Pausas em justificativas e conclusões nos discursos de um sujeito com doença de Parkinson e de um sujeito sem lesão neurológica - Zwarg, Ymorian Vilela [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Biomedical search frequently related pauses in speech of people with Parkinson's disease with motor difficulties caused by this disease. Opposed to this tendency, speech- enunciation search have found semantic- discursive relations involved in the outbreak of breaks in the speech of people with Parkinson's disease. Following this trend, our study investigated the relationship between breaks and speech functioning of a person with Parkinson's disease and a normal person. Thus, we use audio and video recordings - and their transcripts – of the person with Parkinson‟s disease and the normal person talk sessions. In these sessions, the persons had a conversation with an speech therapist interlocutor. Accounted, in their speeches materials, pauses eruptions before occurrences of semantic- discursive mechanism that represent the meaning of justifications and conclusions. The numbers obtained indicted exists strong relationship between breaks and justifications and conclusions. Understood these relationships, we looked for clues in the conversation sessions in order to understand how the justifications and conclusions - and breaks linked to them - they would act in the construction of discursive materiality of the person with a Parkinson‟s disease and a normal person. Thus, we discovery at the speech materials of the person with Parkinson's disease, the speech Health / illness - in which the person with Parkinson‟s disease is placed in the sick position in that his speech therapist interlocutor occupies the post of Supervisor of Health. Also the Foreman speech - in which the person whit a Parkinson disease is placed in the position of instructor in that their interlocutor is placed in the lay position. Identified in the normal person discursive material, the speech Resilience - in which the person is placed in the winner position in that his interlocutor takes the place of spectator. Categorized discursive positions, it was possible to ...

Trabalhos biomédicos frequentemente relacionam pausas na fala de sujeitos com doença de Parkinson às dificuldades motoras causadas por esta doença. Contrapondo-se a essa tendência, trabalhos de orientação enunciativo-discursiva têm encontrado relações semântico-discursivas envolvidas na irrupção de pausas nos discursos desses sujeitos. Seguindo essa tendência, nosso trabalho investigou a relação entre irrupção de pausas e funcionamento discursivo de um sujeito com doença de Parkinson e de um sujeito controle. Para tanto, utilizamos gravações em áudio é vídeo – e suas transcrições – de sessões de conversação desses sujeitos. Nestas sessões, os sujeitos tiveram como interlocutor uma fonoaudióloga. Contabilizamos, em seus materiais discursivos, as pausas irrompidas diante de ocorrências de funcionamentos semântico-discursivos que representam o sentido de justificativas e conclusões. Os números encontrados indiciaram existir forte relação entre pausas e justificativas e conclusões. Compreendidas essas relações, procuramos pistas, nas sessões de conversação dos sujeitos, com o propósito de entender de que maneira as justificativas e conclusões – e as pausas atreladas a elas – agiriam na construção da materialidade discursiva dos sujeitos. Desse modo, pudemos identificar, no material discursivo do sujeito com doença de Parkinson, o discurso Saúde/doença – no qual este sujeito é colocado na posição de Doente na medida em que sua interlocutora fonoaudióloga ocupa o lugar de Orientadora da Saúde. Também, o discurso de Mestre de Obras – no qual este sujeito é colocado na posição de Instrutor na medida em que sua interlocutora é colocada na posição de leiga no assunto. Identificamos, no material discursivo do sujeito controle, o discurso de Superação – no qual o sujeito é colocado na posição de Vencedor na medida em que sua interlocutora ocupa o lugar de Expectadora ...
Keywords: Linguística; Análise linguística; Linguagem; Análise do discurso; Doença de Parkinson; Linguistic analysis (Linguistics)